Atypical Prefrontal–Amygdala Circuitry Following Childhood Exposure to Abuse: Links With Adolescent Psychopathology. (November 2019) - Peverill, Matthew; Sheridan, Margaret A.; Busso, Daniel S.; McLaughlin, Katie A.
Adverse childhood experiences have been associated with more negative coupling between the ventromedial prefrontal cortex (vmPFC) and amygdala, a brain network involved in emotion regulation in both children and adults. This pattern may be particularly likely to emerge in individuals exposed to threatening experiences during childhood (e.g., exposure to child abuse), although this has not been examined in prior research. We collected functional magnetic resonance imaging data on 57 adolescents during an emotion regulation task. Greater negative functional connectivity between vmPFC and amygdala occurred during viewing of negative compared to neutral images. This vmPFC-amygdala task-related functional connectivity was more negative in adolescents exposed to physical, sexual, or emotional abuse than those without a history of maltreatment and was associated with abuse severity. This pattern of more negative functional connectivity was associated with higher levels of externalizing psychopathology concurrently and 2 years later. Greater negative connectivity in the vmPFC-amygdala network during passive viewing of negative images may reflect disengagement of regulatory responses from vmPFC in situations eliciting strong amygdala reactivity, potentially due to stronger appraisals of threat in children exposed to early threatening environments. This pattern may be adaptive in the short term but place adolescents at higher risk of psychopathology later in life.